Health care in the Bible and the Talmud - L.M. Medlen (AOSIS, 1980)
"The thought patterns of occidental civilization have been basically influenced by the mentalities of two peoples: the ancient Greeks, with their lucid reasoning and logical approach to scientific problems, and the People of the Book, with their intuitive ethical teachings, their timeless moral laws, and, last but by no means least, their ethically based health rules." (Rosner, p.3).